Cyclic Fatigue Resistance of Blue Heat-Treated Instruments at Different Temperatures - Thalita Miranda Vieira; Ryhan Menezes Cardoso; Nayane Chagas Carvalho Alves; Silvio Emanuel Acioly Conrado de Menezes; Shirley Machado Batista; Silmara de Andrade Silva; Christianne Velozo; Diana Santana de Albuquerque; Gabriela Queiroz de Melo Monteiro (International Journal of Biomaterials)
The main aim is to evaluate the cyclic fatigue resistance of blue heat-treated instruments with different kinematics. Twenty-four endodontic instruments of the same brand were used for each of three experimental groups: VB (Vortex Blue 40/0.04), RB (RECIPROC Blue 40/0.06), and XB (X1 Blue 40/0.06). The instruments were randomly distributed and subjected to temperatures of 20°C and 37°C. The fatigue test was performed using a stainless steel device. Data were analysed using the Shapiro–Wilk test, Student’s t-test, the F test, and Tukey’s and Tamhane tests at significance level P=0.05. The instruments’ cyclic fatigue resistance at both temperatures differed significantly for each instrument type (P<0.001). The RB instruments displayed greater cyclic fatigue resistance at the tested temperatures compared with the VB and XB instruments (P<0.001). Reciprocating kinematics positively influenced cyclic fatigue resistance. Blue heat-treated instruments showed decreased cyclic fatigue resistance as the temperature increased (P<0.001).